Fatores que influenciam o processo decisório no mercado de engenharia civil em Pau dos Ferros/RN - Azevedo, Wesley Siqueira Carvalho de (Universidade Federal Rural do Semi-Árido, 2019)
The factors that influence the decision making process in the civil engineering market in Pau dos Ferros - RN, characterize the strategies and the efficiency in attracting customers. In this sense, a professional who stands out in the market must have a notion of decisionmaking process to attract clients, however, this subject is little discussed in universities, affecting mainly the class of recent graduates when entering the job market, which is, scarce strategies, as well as social responsibility and interpersonal relationship between client and engineer. This paper seeks to answer the following research questions: What influences the client most when hiring a civil engineering professional? And what strategies do civil engineers use to prospect sales? Therefore, this study aims to analyze the factors that influence the contracting of services and which strategies civil engineers use in capturing clients, as well as demonstrate the usefulness of the decision making process by the need for further study. For the development of this work were deepened studies about the bibliography referring to the management process in the construction, about the decision making process and the marketing plan. The survey was conducted using a printed questionnaire, which revealed that even in a cyclical civil engineering market, there are times when it is bad and in others it is good for closing services, and the economy contributes a lot to that. However, in response to changes in the labor market, engineers are improving new ways of engaging in both customer acquisition strategies and organizational structures.
Keywords: Estratégias; Captação de clientes; Plano de marketing; Strategies; Customer acquisition; Marketing plan; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA